A novel prison mental health in-reach service in Somaliland: a model for low-income countries?. Issue 3 (August 2014) - Handuleh, Jibril I. M.; Mclvor, Ronan J.
Abstract : Prison in-reach mental health services are reasonably well developed in advanced economies, but virtually nonexistent in low-and middle-income countries. We describe the development of a small prison in-reach project in Somaliland, a self-declared independent state which has experienced conflict and poverty in equal measure. After careful planning and cooperation with local agencies, the service provides sessional input to a regional prison, including assessment and treatment of a wide range of psychiatric conditions. The project has had some unexpected benefits, which are described. The success of the project reflects the effectiveness of collaboration between local stakeholders and international agencies, and could be used as a model for the development of in-reach services in other low-income countries.